Prenatal dioxin exposure and glucose metabolism in the Seveso Second Generation study. (January 2020) - Warner, Marcella; Rauch, Stephen; Brambilla, Paolo; Signorini, Stefano; Mocarelli, Paolo; Eskenazi, Brenda
Highlights: The Seveso Second Generation study is a cohort of children born to TCDD-exposed women. We examined associations of in utero TCDD exposure with glucose homeostasis. In utero TCDD exposure was associated with lower insulin resistance in females only. Observed associations in daughters showed evidence of mediation by body mass index. Abstract: Background: Exposure to endocrine disrupting compounds such as 2, 3, 7, 8-tetrachlorodibenzo- p -dioxin (TCDD) during susceptible developmental windows may alter risk of metabolic disease later in life. Animal studies of in utero and lactational TCDD exposure report associations with alterations in insulin sensitivity and energy homeostasis, but epidemiologic evidence is limited. We examined the relationship of prenatal TCDD exposure with markers of glucose homeostasis in the Seveso Second Generation study, a unique cohort of children born to TCDD-exposed women resulting from a 1976 explosion in Seveso, Italy. Methods: We included 426 children who were 18 years or older with complete follow-up data including a fasting blood draw. Insulin and glucose were measured and the updated homoeostatic model assessment was used to estimate insulin resistance (HOMA2-IR) and beta-cell function (HOMA2-B). Prenatal TCDD exposure was defined in two ways, as initial maternal serum TCDD concentration and TCDD estimated at pregnancy. Results: The children (222 female, 204 male) averaged 28.6 (±6.0) years. We found a 10-fold increase in TCDD estimated at pregnancy was inversely associated with insulin (adj-β = −1.24 μIU/mL, 95% confidence interval (CI): −2.38, −0.09) and HOMA2-B (adj-β = −10.2% decrease, 95% CI: −17.8, −1.9) among daughters, but not sons (insulin: adj-β = 0.57 μIU/mL, 95% CI: −0.84, 1.98, P for interaction = 0.04; and HOMA2-B: adj-β = 0.8% increase, 95% CI −10.7, 13.9, P for interaction = 0.11). Similar effect modification was observed for TCDD estimated at pregnancy and HOMA2-IR ( P for interaction = 0.13). The models for initial maternal serum TCDD showed similar effect modification by child sex. The observed associations in daughters showed evidence of mediation by body mass index, which we have previously found to be associated with prenatal TCDD exposure in female offspring. Conclusion: These results suggest prenatal exposure to TCDD is associated with lower insulin resistance and beta compensation in female offspring, and show evidence of mediation by body mass index.